Compensating Injury to Autonomy in English Negligence Law: Inconsistent Recognition. (10th April 2018) - Keren-Paz, Tsachi
Abstract: Recently in Shaw v Kovac, the Court of Appeal seemed to have rejected a standalone injury to autonomy (ITA) as actionable in negligence, in an informed consent case. In this article, I argue that Shaw can be explained away, and that English law recognizes ITA as actionable in a series of cases, some of which— Bhamra, Tracey, and Yearworth —were not hitherto understood to do so. However, the under-theorization in the cases leads to inconsistencies. Like cases ( Rees / Yearworth ; Chester / Tracey ) are not treated alike; ITA is misunderstood to be about 'religious offence' ( Bhamra ) and property loss ( Yearworth ) and worse still, the more serious type 2 ITA ( Rees ) gives rise to a weaker remedy (of exceptional nature aside) than the less serious type 1 injury ( Chester ). A better understanding of the different manifestations of ITA will lead to results which are both more consistent and more justified on the merit.